Even non-expert radiologists report chronic thromboembolic pulmonary hypertension (CTEPH) on CT pulmonary angiography with high sensitivity and almost perfect agreement - Hrdlicka, Jan; Jurka, Martin; Bircakova, Bianka; Ambroz, David; Jansa, Pavel; Burgetova, Andrea; Lambert, Lukas (European radiology, 2024)
OBJECTIVES: To assess the diagnostic performance and interobserver agreement of CT pulmonary angiography (CTPA) in the detection of chronic thromboembolic pulmonary hypertension (CTEPH) and its features among radiologists of different levels of experience. MATERIALS AND METHODS: In this retrospective, single-center, single-blinded study, three radiologists with different levels of experience in CT imaging (R1:15 years, R2:6 years, and R3:3 years) evaluated CTPA of 51 patients ultimately diagnosed with CTEPH (European Society of Cardiology guidelines) and 49 patients without CTEPH in random order to assess the presence of CTEPH, its features in the pulmonary artery tree, proximal level of involvement, bronchial artery hypertrophy, mosaic perfusion, and right heart overload. RESULTS: CTPAs of 51 patients with CTEPH (median age, 66 years (IQR 56-72), 28 men) and 49 patients without CTEPH (median age, 65 years (IQR 50-74), 25 men) were evaluated. The sensitivity and specificity for the detection of CTEPH was 100% (all radiologists) and 100% (R1), 96% (R2), and 96% (R3) with almost perfect agreement (κ = 0.95). The sensitivity and specificity for detecting CTEPH by mosaic perfusion would be 89% (95%CI 83-93%) and 81% (74-87%). The level of pulmonary artery involvement was reported with moderate agreement (κ = 0.54, 95%CI 0.40-0.65). Substantial agreement was found in the evaluation of mosaic attenuation (κ = 0.75, 95%CI 0.64-0.84), right heart overload (κ = 0.68, 95%CI 0.56-0.79), and bronchial artery hypertrophy (0.71, 95%CI 0.59-0.82) which were the best predictors of CTEPH (p < 0.0001). CONCLUSIONS: CTPA has high sensitivity and specificity in detecting CTEPH and almost perfect agreement among radiologists of different levels of expertise. CLINICAL RELEVANCE: CT pulmonary angiography can be used as a first-line imaging modality in patients with suspected chronic thromboembolic pulmonary hypertension (CTEPH) even when interpreted by non-CTEPH experts. KEY POINTS: • CT pulmonary angiography has high sensitivity and specificity in detecting chronic thromboembolic pulmonary hypertension (CTEPH) and almost perfect interobserver agreement among radiologists of different levels of expertise. • Substantial agreement exists in the assessment of mosaic attenuation, right heart overload, and bronchial artery hypertrophy, which are the best predictors of CTEPH.
Keywords: senioři; hypertrofie; Pulmonary Embolism; Pulmonary embolism; Pulmonary artery; Computed tomography angiography; angiografie; Retrospective Studies; Tomography, X-Ray Computed; Chronic Disease; Single-Blind Method; chronická nemoc; plicní embolie; Hypertension, Pulmonary; Middle Aged; mužské pohlaví; jednoduchá slepá metoda; plicní hypertenze; ženské pohlaví; Angiography; retrospektivní studie; Humans; Hypertrophy; lidé středního věku; Pulmonary arterial hypertension; počítačová rentgenová tomografie; Aged; Female; lidé; Male